Evaluation of the nutritional value of bee pollen by palynological, antioxidant, antimicrobial, and elemental characteristics - YOLCU, UFUK (My University, 2022)
The object of this study was to characterize bee pollen (BP) as a food supplement according to its palynological, antioxidant, antimicrobial properties, and elemental contents. Twelve plant families, 35 genera, and one species were determined by palynological analysis of BP. Verbascum spp., Papaver spp., and Vicia spp. were found the major floral sources of BP. Two samples were determined as monofloral Verbascum spp. bee pollen. Total flavonoid (TFC) and phenolic content (TPC) varied from 117.5 to 142.09 mg QE/100 g, and 386.59 to 743.73 mg GAE/100 g, respectively. According to 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical and 2,2\"-azino-bis3-ethylbenzothiazoline-6-sulfonic acid (ABTS) radical cation assays, the BP samples demonstrated high antioxidant activity. Result of ferric reducing antioxidant power (FRAP) and metal chelating activities (MCA) assays were ranging from 61.17 to 69.7% and 74.99 to 87.78%. Antimicrobial activities of the BP were determined by the agar well diffusion and microplate method. Obtained results indicated that BP showed appreciable antibacterial activity against Escherichia coli, Bacillus cereus, and Staphylococcus aureus strains by remarkably decreasing bacterial growth. Thirty-one elements were analyzed in BP samples by inductively coupled plasma-mass spectrometry (ICP-MS). Target hazard quotients (THQ), hazard index (HI), and estimated daily intake (EDI) values were calculated using selected elements\" results. Considering these values, it was determined that the consumption of bee pollen was safe for adults and children. BP samples can be used as a food supplement because of their high antioxidant and antimicrobial capacity and elemental content.
Keywords: Tarımsal Bilimler; Ziraat; Gıda Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Food Engineering; Engineering and Technology; GIDA BİLİMİ VE TEKNOLOJİSİ; Tarım Bilimleri; Tarım ve Çevre Bilimleri (AGE); FOOD SCIENCE & TECHNOLOGY; AGRICULTURAL SCIENCES; Agriculture & Environment Sciences (AGE); Yemek bilimi; Yaşam Bilimleri; Food Science; Life Sciences